Integrated assessment and modeling of regional recycling of organic waste. (15th December 2022) - Misslin, Renaud; Clivot, Hugues; Levavasseur, Florent; Villerd, Jean; Soulié, Jean-Christophe; Houot, Sabine; Therond, Olivier
Abstract: Recycling organic waste in agriculture is an important component of strategies that address global and local challenges, such as soil carbon storage and fertility. However, using organic waste as fertilizer can also induce unintended pollution. These combined impacts can be understood through the perspective of a social-ecological system and studied using an integrated assessment and modeling approach. Presently, no tool completely enables stakeholders to grasp the multiple tradeoffs and synergies among biomass-management strategies while considering the unique characteristics and heterogeneity of their region. This article introduces MAELIA-OWM, an integrated assessment and modeling platform that aims to fill this gap. To illustrate the platform's abilities, MAELIA-OWM was applied to the Versailles Plain, France. Two scenarios of organic waste recycling with increased use of organic waste were compared to a baseline mineral fertilization scenario using a set of agro-environmental and socioeconomic indicators. The results predicted that increasing organic fertilization in the Versailles Plain would increase fertilization costs and workload, slightly increase nitrogen losses but improve soil quality through soil carbon storage. Results also highlighted that impacts of intensive organic fertilization on the overall greenhouse gas balance depends on the methods used to allocate greenhouse gas emissions between producers and/or users of organic waste. When shared on a 50-50 basis between upstream activities and downstream agricultural production, greenhouse gas emissions are equivalent across all three scenarios. The "potential mineral and organic practices" scenario improves soil quality but increases production costs and nitrate leaching risks. Therefore, based on these simulations, increasing organic fertilization can be considered as a step forward into the agroecological transition but requires careful use by and compensation for farmers. Graphical abstract: Image 1